Multiresponsive Supramolecular Theranostic Nanoplatform Based on Pillar[5]arene and Diphenylboronic Acid Derivatives for Integrated Glucose Sensing and Insulin Delivery. Issue 38 (2nd August 2018) - Zuo, Minzan; Qian, Weirui; Xu, Zuqiang; Shao, Wei; Hu, Xiao‐Yu; Zhang, Dongmei; Jiang, Juli; Sun, Xiaoqiang; Wang, Leyong
Abstract: A closed‐loop "smart" insulin delivery system with the capability to mimic pancreatic cells will be highly desirable for diabetes treatment. This study reports a multiple stimuli‐responsive insulin delivery platform based on an explicit supramolecular strategy. Self‐assembled from a well‐designed amphiphilic host–guest complex formed by pillar[5]arene and a diphenylboronic acid derivative and loaded with insulin and glucose oxidase, the obtained insulin‐GOx‐loaded supramolecular vesicles can selectively recognize glucose, accompanied by the structure disruption and efficient release of the entrapped insulin triggered by the high glucose concentration as well as the in situ generated H2 O2 and acid microenvironment during the GOx‐promoted specific oxidation of glucose into gluconic acid. Moreover, such a "smart" supramolecular theranostic nanoplatform is able to function as both a glucose sensor and a controlled insulin delivery actuator. In vivo experiments further demonstrate that this smart supramolecular nanocarrier shows fast response to hyperglycemic circumstances and can effectively regulate the glucose levels in a mouse model of type I diabetes. Abstract : A closed‐loop insulin delivery platform is developed based on a supramolecular strategy. This multiple stimuli‐responsive system can respond to glucose, as well as the in situ generated H2 O2 and acidic microenvironment. Moreover, such a "smart" theranostic nanoplatform can simultaneously realize blood glucose monitoring and controlled insulin delivery.